An iterative method for the linearization of nonlinear failure criteria. (March 2018) - Sharan, S.K.
Highlight: A novel general method is proposed for the linearization of nonlinear failure criteria. The method may be used to analyze problems in structural and geotechnical engineering involving materials governed by nonlinear yield functions for which computer software are not available. The proposed method is shown to be convergent, efficient and effective. Abstract: Linearization of a nonlinear failure criterion may be required if a software incorporating the nonlinear failure criterion is not readily available or if an additional computational difficulty is encountered due to the nonlinearity of the failure criterion. In this paper, a novel method is proposed for the linearization of nonlinear failure criteria. The proposed method is based on an iterative procedure and the least-squares regression is used for the linearization. The material is assumed to be elastic-perfectly plastic. By conducting analytical and finite element analyses of stresses and displacements around underground openings in rock mass governed by the generalized Hoek–Brown failure criterion, it is shown that the proposed method is convergent, efficient and effective.